In vitro Effect of Photodynamic Therapy with Curcumin and Methylene Blue Photosensitizers on Staphylococcus Aureus - Sarvin Entezari; Nahid Moezzimoghadam; Shirin Lawaf; Arash Azizi (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Staphylococcus aureus (S.A) can colonize in the skin, nasal cavity, and oral cavity. In the oral cavity, it can cause dental caries and periodontal disease. Mouthwashes can be used as an adjunct to mechanical plaque control methods to decrease the load of oral microorganisms. Chlorhexidine (CHX) is a commonly used antimicrobial mouthwash with side effects such as changing the sense of taste, tooth discoloration, oral mucosal burning, allergy, and xerostomia. It also has adverse systemic effects, if swallowed. Purpose: This study aimed to assess the effect of photodynamic therapy (PDT) with curcumin and methylene blue (MB) photosensitizers and different laser parameters on S.A colony count. Materials and Method: In this in vitro experimental study, 99 samples of standard-strain S.A were subjected to PDT with curcumin and MB photosensitizers with/without irradiation of 660 and 445 nm laser with different exposure parameters, and CHX in 9 groups (n=11). The samples were cultured in microplates containing Mueller-Hinton agar, and the number of colony forming units (CFUs) was counted after 24 h of incubation at 37°C. Data were analyzed by the Kruskal-Wallis and Dunn tests. Results: The minimum colony count was noted in CHX group (CFUs=0) followed by MB and 660nm diode laser group irradiated for 100 s (CFUs=147.2727±169.35707). The difference in this respect was significant between MB+660nm diode laser for 100 s and other groups (p< 0.05) except for the MB + 660 nm diode laser for 60 s group. Conclusion: CHX is superior to laser for elimination of S.A. However, PDT with 660 nm diode laser + MB has considerable antimicrobial efficacy against S.A; increasing the duration of laser irradiation enhances the antimicrobial effect.